(untitled) (Research, Society and Development, 2020)
In recent years, due to the appeal for the use of materials that cause less impact on the environment, the rationalization and use of wood has become a requirement, as it is a material with great potential to be used in different sectors of the economy. Its use as a structural element in recent years is related to the increase in the technology used in its processing, such as the industrialization of wooden structures, the use of reforestation species and the use of preserving agents with higher quality. The Amazon is characterized by being a region with great potential for wood producing forests of the most varied species. Greater knowledge of the physical and mechanical properties of wood is essential to rationalize the use of this raw material. Lately, research to clarify the properties of wood is increasing, however, there is still much to discover. This work aims to evaluate four species of Amazonian woods Cedrorana (Cedrelingacateniformis), Piquiarana (Caryocarglabrum and C. villosum), Tauari (Carinianamicranta) and Macacaúba (Platymiscium ulei) used in civil construction. Their densities and mechanical properties of compression parallel to the fibers, normal flexion to the fibers and screw pullout were evaluated. As density is one of the most important properties regarding the indication of uses for wood, and being one of the properties that provides more information about its characteristics, with the results obtained it was observed that the mechanical tests have a correlation with density.